Incidence of fractures in people with intellectual disabilities over the life course: a retrospective matched cohort study. (October 2022) - Frighi, Valeria; Smith, Margaret; Andrews, Tim M.; Clifton, Lei; Collins, Gary S.; Fuller, Alice; Roast, Jan; Holt, Tim A.
Summary: Background: Current osteoporosis guidelines do not identify individuals with intellectual disabilities (ID) as at risk of fracture, potentially missing opportunities for prevention. We aimed to assess the incidence of fractures in people with ID over the life course. Methods: Descriptive analysis of open cohort study using anonymised electronic health records from the UK Clinical Practice Research Datalink, linked to the Hospital Episode Statistics database (Jan 1, 1998–Dec 31, 2017). All individuals with ID were matched on age and sex to five individuals without ID. We calculated the incidence rate (95% CI) per 10000 person-years (py) and incidence rate ratio (IRR, 95% CI) to compare fractures between individuals with and without ID (age 1–17 and ≥18 years) for any fracture, and in those aged 18–49 and ≥ 50 years for major osteoporotic fracture (vertebra, shoulder, wrist, hip), and for hip fracture. Findings: 43176 individuals with ID (15470 children aged 1–17 years; 27706 adults aged ≥ 18 years) were identified and included (40.4% females) along with 215733 matched control individuals. The median age at study entry was 24 (10th–90th centiles 3–54) years. Over a median (10th–90th centile) follow-up of 7.1 (0.9–17.6) and 6.5 (0.8–17.6) years, there were 5941 and 24363 incident fractures in the ID and non ID groups respectively. Incidence of any fracture was 143.5 (131.8–156.3) vs 120.7 (115.4–126.4)/10000 py (children), 174.2 (166.4–182.4)/10000 py vs 118.2 (115.3–121.2)/10000 py (adults) in females. In males it was 192.5 (182.4–203.2) vs 228.5 (223.0–234.1)/10000 py (children), 155.6 (149.3–162.1)/10000 py vs 128.4 (125.9–131.0)/10000 py (adults). IRR for major osteoporotic fracture was 1.81 (1.50–2.18) age 18–49 years, 1.69 (1.53–1.87) age ≥ 50 years in women. In men it was 1.56 (1.36–1.79) age 18–49 years, 2.45 (2.13–2.81) age ≥ 50 years. IRR for hip fracture was 7.79 (4.14–14.65) age 18–49 years, 2.28 (1.91–2.71) age ≥ 50 years in women. In men it was 6.04 (4.18–8.73) age 18–49 years, 3.91 (3.17–4.82) age ≥ 50 years. Comparable rates of major osteoporotic fracture and of hip fracture occurred approximately 15 and 20 years earlier respectively in women and 20 and 30 years earlier respectively in men with ID than without ID. Fracture distribution differed profoundly, hip fracture 9.9% vs 5.0% of any fracture in adults with ID vs without ID. Interpretation: The incidence, type, and distribution of fractures in people with intellectual disabilities suggest early onset osteoporosis. Prevention and management strategies are urgently required, particularly to reduce the incidence of hip fracture. Funding: National Institute for Health and Care Research.